The Validation of Drug Resistance in Pneumonia (DRIP) Score in Predicting Infections due to Drug-Resistant Pathogens in Community-acquired Pneumonia at Cipto Mangunkusumo Hospital, Jakarta, Indonesia - Fadrian Fadrian; Khie Chen; July Kumalawati; Cleopas M Rumende; Hamzah Shatri; Erni J Nelwan (Interna Publishing, 2022)
Background: The emergence of drug-resistant pathogens (DRP) in recent years possibly contributes to the common problems associated with community-acquired pneumonia. However, to predict the risk of the ailment, the DRIP score is mainly applied, although no validation study has been reported in Indonesia. Therefore, the score prediction accuracy in the population, patient characteristics and germ patterns appears indefinite, particularly for Cipto Mangunkusumo Hospital, Jakarta. The purpose of this study is to determine the DRIP performance as an instrument in predicting infections due to drug-resistant pathogens (DRP) in community-acquired pneumonia at Cipto Mangunkusumo Hospital. Methods: This research employed a cross-sectional design, where the subjects were community-acquired pneumonia patients treated between January 2019 and June 2020. In addition, adequate medical records of the participants were obtained. The condition is defined as DRP when the sputum culture results show resistance to non-pseudomonal β-lactam antibiotics, macrolides, and respiratory fluoroquinolones. Furthermore, the score performance was analyzed by determining the calibration and discrimination values, using the Hosmer-Lemeshow test and AUROC, respectively. Results: A total of 254 subjects were known to have satisfied the selection criteria. These participants were categorized into DRP and non-DRP groups, with 103 (40.6%) and 151 (59.4%) patients, correspondingly. The DRIP calibration analysis using the Hosmer-Lemeshow test obtained p-value = 0.001 (p <0.05), while an AUC value of 0.759 (CI 95%, 0.702-0.810) was derived from the ROC curve. However, at a score of ≥ 4, the DRIP showed sensitivity, specificity, positive and negative predictive values of 70.9, 92.7, 86.9, and 82.3%, respectively. Conclusion: The DRIP score demonstrated a significant performance in predicting infections due to DRP in community-acquired pneumonia.